Live streaming E-commerce platform characteristics: Influencing consumer value co-creation and co-destruction behavior - Wang, Lei; Zhang, Ru-Shui; Zhang, Cheng-Xin (Acta psychologica, 2024)
Live streaming with goods is developing rapidly as an emerging platform economic model. Consumers can interact with the e-commerce platform in real-time and get a good shopping experience. This in turn generates value co-creation behaviors such as word-of-mouth communication. However, due to the lack of effective audit mechanisms on some platforms, the phenomenon of value co-destruction among them is becoming more and more common. This brings value loss to consumers, e-commerce platforms, and other multiple subjects. Based on the SOR model, this paper collects 212 sample data by using a questionnaire survey. The impact of live banding platform characteristics on consumers' value co-creation and value co-destruction behaviors is analyzed through multiple regression and other methods. The results show that platform information quality, functional quality, and interactive quality all positively affect consumers' value co-creation behavior and negatively affect value co-destruction behavior. Perceived value plays a mediating role, and promotional incentives enhance the positive relationship between platform features and perceived value. Therefore, if the live streaming bandwagon platform provides consumers with sufficiently rich, complete, and timely product information, responds quickly to consumer needs, and has high interaction quality. Consumers are more likely to exhibit value co-creation behavior. This study enriches the theoretical results of value co-creation and value co-destruction. It provides theoretical references for live streaming platforms to inhibit consumers' value co-destructive behaviors and promote value co-creation behaviors. In practice, it is pointed out that live streaming platforms should provide consumers with real information on all aspects of the products, update and improve the performance of the platform in a timely manner, and provide regular training to the staff.